Generating a plurality of disjoint paths in networks, the application of the algorithm "BACKWARD WAVE" - Кулаков, Ю. А.; Коган, А. В.; Диброва, М. А.; Чхаидзе, Д. М. (Problems of Informatization and Control, 2015)
The problems of multipath routing in computer networks of large dimension. A brief overview of how multipath routing. The feasibility of the use of "reverse wave" of algorithms in conjunction with the method of "branch and bound" to optimize the process of forming a plurality of disjoint paths provides a method of forming a plurality of non-intersecting paths through the trees at the junction box computer network. An algorithm for the formation of a plurality of disjoint paths using "reverse wave" algorithm